Analysis of the gasoline price in colombia: approximation (2010)
This paper presents an analysis of the price structure of gasoline in Colombia from 1999 to 2009, by doing a comparison of the resolution with which the Colombian government sets the actual price regarding the public sale price in general in the different service stations. The beginning shows how the WTI price influences the gasoline prices in countries such as United States, Venezuela, and France, but for Colombia the relation is not clear yet. Then the article exposes the factors used to set the price of gasoline in Colombia. Finally, it is concluded that the price of Colombian gasoline is very high and does not follow the equation proposed by the government and the factors that have the most influence on the final price are the producer income mainly affected by the WTI and the Market Representative Rate.